Evolving therapies for non-alcoholic steatohepatitis. (June 2014) - Tilg, Herbert; Moschen, Alexander R
<x xml:space="preserve">Abstract</x> Introduction: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease in the world. Approved therapies for this disorder, however, are still lacking. In the last decade, pathophysiological insights into this disease have been tremendous. Various aspects, such as insulin resistance, innate immunity, metabolic inflammation and the microbiota, have been characterized as major players. Indeed, at least 1 in 10 sufferers will have the disease escalate toward its inflammatory phenotype, non-alcoholic steatohepatitis (NASH). These pathways currently represent the most attractive treatment targets. Furthermore, interference with insulin resistance has shown some efficacy in the past, although more focused therapies, which also act anti-inflammatory, are needed. Areas covered: In this review, the authors highlight the current most promising treatment strategies in NASH/NAFLD. Expert opinion: Treatment of NAFLD is still in its infancy, although large controlled studies have demonstrated some efficacy for pioglitazone or vitamin E. The natural course of this disease demands long-term treatments besides diet and lifestyle changes. Based on the current view of NAFLD pathophysiology, effective therapies have to target metabolic inflammation, glucose and lipid metabolism. The search for agents interfering with all of these pathways has recently generated promising candidates for the treatment of NAFLD such as farnesoid X receptor, peroxisome proliferator-activated receptor-α/δ agonists or AdipoR small-molecule agonists.